Testicular apoptotic activity in two bio-sentinel fish species inhabiting an aquatic ecosystem in an area where continual DDT spraying occurs : utility of immunohistochemical assays - Van Dyk, Jacobus C. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2008.